CLINICAL AND ANTHROPOMETRIC CHARACTERISTICS OF NUTRITIONAL STATUS IN CHILDREN WITH CONGENITAL HEART DISEASE AND CHRONIC HEART FAILURE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Nutritional status impairment is one of the most common comorbid conditions in infants with congenital heart disease (CHD), especially when accompanied by chronic heart failure (CHF) [1,6]. Increased energy expenditure, chronic hypoxia, and limited feeding tolerance create conditions for early development of protein–energy deficiency during the first year of life [6–8]. The aim of this study was to evaluate the clinical and anthropometric characteristics of nutritional status in infants with CHD complicated by CHF. A total of 50 children aged 1–12 months were examined. Nutritional assessment was performed using WHO growth standards, anthropometric indices, and clinical evaluation of heart failure severity [1,9]. The results demonstrated a high prevalence of moderate and severe malnutrition, primarily manifested by body weight deficit and depletion of muscle and fat stores. More pronounced nutritional disorders were observed in children with cyanotic CHD and higher functional classes of CHF. The obtained data confirm the importance of early identification of nutritional deficiency in infants with CHD to prevent progression of growth retardation and adverse clinical outcomes.